Crop rotation enhances yield and water productivity: Uncovering potential drivers through global field experiment synthesis - Liangang Xiao; Yudi Wang; Chenxi Zhang; Kebing Zhao; Rongqin Zhao; Zhixiang Xie (Agricultural Water Management)
Crop yield, crop water productivity (WPc), and crop evapotranspiration (ETc) represent three essential ecological metrics for evaluating sustainable intensification strategies in cropland management. However, integrated analyses of crop rotation’s effects on these parameters remain underexplored, obscuring mechanistic understanding of how rotation practices drive productivity gains through optimized water use. Based on 1217 pairs of field experimental data across global croplands, we systematically quantified rotation-induced modifications in yield-water dynamics of five major food crops and identified the key environmental and agronomic drivers. Key findings demonstrated significant rotation-driven enhancements in yield (+13.2 %) and WPc (+17.6 %), coupled with reduced ETc (-6.2 %). Higher improvement of crop yield and WPc was observed for potato as compared to wheat, maize, soybean and rice, while multi-crop sequences outperformed simple rotations. A complete duration of rotation cycle of ≥ 2 year seemed more suitable for maintaining higher benefits in yield and WPc. Crop rotation performed better in soils with pH < 6.5 and regions with MAP < 500 mm. Although irrigation regimes showed negligible influence, nitrogen inputs exhibited strict thresholds (< 120 kg ha⁻¹) for maximizing yield and WPc increase. Notably, rotational advantages were confined to conventional tillage systems, demonstrating limited synergy with no-till/residue retention practices. The observed ETc reduction revealed water-saving mechanisms through preferential transpiration enhancement over evaporation suppression. This study illustrates crop rotation as a dual-function strategy that concurrently addresses yield enhancement and water conservation, which positions crop rotation as indispensable components of conservation agriculture. The findings may provide valuable insights for enhancing crop rotation strategies through species-specific chronological arrangements, environmental compatibility assessments, and precision agricultural practices.